Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s13273-011-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of gene expression by crotonaldehyde in human umbilical vein endothelial cells

Abstract: Crotonaldehyde (CRA) is an α,β-unsaturated aldehyde that is genotoxic, carcinogenic, and mutagenic, and forms 1,N(2)-propanodeoxyguanosine. Humans are exposed to CRA in work places, and from tobacco smoke, environmental pollution, food, and beverages. In addition, CRA is a product of endogenous lipid peroxidation, arising as a consequence of oxidative stress and electrophilic stress, which may be related to development of cardiovascular diseases. In this study, we used 24 k whole human DNA chips for identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There is increasing evidence that α,β-unsaturated aldehydes in CS, including acrolein and crotonaldehyde play an important pathophysiological role in vascular diseases such as atherosclerosis and Alzheimer's disease. Exposure to α,β-unsaturated aldehydes is critical to the inflammatory response via activation of the proinflammatory signaling pathway and redox-sensitive transcription factors [27,28] . Furthermore, α,β-unsaturated aldehydes increase oxidative stress [29] , which plays a crucial role in the pathogenesis of vascular diseases via direct injury to the endothelium [30] .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that α,β-unsaturated aldehydes in CS, including acrolein and crotonaldehyde play an important pathophysiological role in vascular diseases such as atherosclerosis and Alzheimer's disease. Exposure to α,β-unsaturated aldehydes is critical to the inflammatory response via activation of the proinflammatory signaling pathway and redox-sensitive transcription factors [27,28] . Furthermore, α,β-unsaturated aldehydes increase oxidative stress [29] , which plays a crucial role in the pathogenesis of vascular diseases via direct injury to the endothelium [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from dorsal skin lesions using the TRIzol (ambion, 15596026) method [ 31 ]. RNA (1 µg) was used as a template to synthesize cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have revealed that crotonaldehyde reduces glutathione (GSH) levels and enhances the levels of intracellular reactive oxygen species (ROS), leading to a state of vulnerability in human airway cells [2] , [11] . Crotonaldehyde has been reported to modulate biological reactions by a variety of downstream signaling pathways [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%